Caryopathic effect of extract Fasciola hepatica on laboratory mice - E. V. Krasnikova; T. N. Sivkova (Российский паразитологический журнал, 2016)
Effect of extract of trematodes Fasciola hepatica on body cells of laboratory mice is studied. A single intraperitoneal injection of rectified extract of fascioles was made into non-linear white male mice at the dose of 100 mg/kg of extract en- zyme. The total number of leucocytes, lymphocytes, monocytes and granulocytes has been registered. Blood films as well as red bone marrow- and seminal vesicles smears were stained using a Romanowsky - type stain and microscoped. Mitotic index was determined and number of abnormal mitotic figures calculated. It is found that a single intraperitoneal injection of rectified extract F. hepatica into non-linear white male mice increases the number of aneuploid cells of red bone marrow as well as stimulates production of lymphocytes and eosinophils. The re- ceived results confirm the ability of helminths to cause the host cell mitotic distur- bances